Relationship between Socio-Economic Status, Interpersonal Communication, and School Climate with Parental Involvement in Early Childhood Education - Endrika; Sujarwo; Achmad, Said Suhil (Jurnal Pendidikan Usia Dini, 2020)
Parental Involvement in their children's schooling has long been recognized as a critical component of good education. This study aims to find out the relationship between socioeconomic status, interpersonal communication, and school climate with parental involvement in early childhood education. Using survey and correlational research design, data collection was carried out through accumulation techniques with tests and questionnaires. The data analysis technique used statistical analysis and multiple regressions. The findings in the socio-economic context of parents show that the measure of power is an indicator in the very high category with a total score of 5, while the measures of wealth, honour and knowledge are included in the high category with a total score of 4 in relation to parental involvement. The form of interpersonal communication, the openness of parents in responding happily to information / news received from schools about children is a finding of a significant relationship with parental involvement in early childhood education. The school climate describes the responsibility for their respective duties and roles, work support provided, and interpersonal communication relationships, parents at home and teachers at school. Keywords: Socio-economic Status, Interpersonal Communication, Climate School, Parental Involvement, Early Childhood Education References Amato, P. R. (2005). The Impact of Family Formation Change on the Cognitive, Social, and Emotional Well-Being of the Next Generation. The Future of Children, 15(2), 75–96. https://doi.org/10.1353/foc.2005.0012 Arnold, D. H., Zeljo, A., Doctoroff, G. L., & Ortiz, C. (2008). Parent Involvement in Preschool: Predictors and the Relation of Involvement to Preliteracy Development. School Psychology Review, 37(1), 74–90. https://doi.org/10.1080/02796015.2008.12087910 Barbato, C. A., Graham, E. E., & Perse, E. M. (1997). Interpersonal communication motives and perceptions of humor among elders. Communication Research Reports, 14(1), 48–57. https://doi.org/10.1080/08824099709388644 Barbato, C. A., Graham, E. E., & Perse, E. M. (2003). Communicating in the Family: An Examination of the Relationship of Family Communication Climate and Interpersonal Communication Motives. Journal of Family Communication, 3(3), 123–148. https://doi.org/10.1207/S15327698JFC0303_01 Barnard, W. M. (2004). Parent involvement in elementary school and educational attainment. Children and Youth Services Review, 26(1), 39–62. https://doi.org/10.1016/j.childyouth.2003.11.002 Benner, A. D., Boyle, A. E., & Sadler, S. (2016). Parental Involvement and Adolescents’ Educational Success: The Roles of Prior Achievement and Socioeconomic Status. Journal of Youth and Adolescence, 45(6), 1053–1064. https://doi.org/10.1007/s10964-016-0431-4 Berkowitz, R., Astor, R. A., Pineda, D., DePedro, K. T., Weiss, E. L., & Benbenishty, R. (2021). Parental Involvement and Perceptions of School Climate in California. Urban Education, 56(3), 393–423. https://doi.org/10.1177/0042085916685764 Berkowitz, R., Moore, H., Astor, R. A., & Benbenishty, R. (2017). A Research Synthesis of the Associations Between Socioeconomic Background, Inequality, School Climate, and Academic Achievement. Review of Educational Research, 87(2), 425–469. https://doi.org/10.3102/0034654316669821 Brand, S., Felner, R. D., Seitsinger, A., Burns, A., & Bolton, N. (2008). A large-scale study of the assessment of the social environment of middle and secondary schools: The validity and utility of teachers’ ratings of school climate, cultural pluralism, and safety problems for understanding school effects and school improvement. Journal of School Psychology, 46(5), 507–535. https://doi.org/10.1016/j.jsp.2007.12.001 Brand, S., Felner, R., Shim, M., Seitsinger, A., & Dumas, T. (2003). Middle school improvement and reform: Development and validation of a school-level assessment of climate, cultural pluralism, and school safety. Journal of Educational Psychology, 95(3), 570–588. https://doi.org/10.1037/0022-0663.95.3.570 Culp, A. M., Hubbs-Tait, L., Culp, R. E., & Starost, H.-J. (2000). Maternal Parenting Characteristics and School Involvement: Predictors of Kindergarten Cognitive Competence Among Head Start Children. Journal of Research in Childhood Education, 15(1), 5–17. https://doi.org/10.1080/02568540009594772 Dearing, E., McCartney, K., Weiss, H. B., Kreider, H., & Simpkins, S. (2004). The promotive effects of family educational involvement for low-income children’s literacy. Journal of School Psychology, 42(6), 445–460. https://doi.org/10.1016/j.jsp.2004.07.002 Desforges, C., Abouchaar, A., Great Britain, & Department for Education and Skills. (2003). The impact of parental involvement, parental support and family education on pupil achievements and adjustment: A literature review. DfES. El Nokali, N. E., Bachman, H. J., & Votruba-Drzal, E. (2010). Parent Involvement and Children’s Academic and Social Development in Elementary School: Parent Involvement, Achievement, and Social Development. Child Development, 81(3), 988–1005. https://doi.org/10.1111/j.1467-8624.2010.01447.x Englund, M. M., Luckner, A. E., Whaley, G. J. L., & Egeland, B. (2004). Children’s Achievement in Early Elementary School: Longitudinal Effects of Parental Involvement, Expectations, and Quality of Assistance. Journal of Educational Psychology, 96(4), 723–730. https://doi.org/10.1037/0022-0663.96.4.723 Epstein, J. L. (Ed.). (2002). School, family, and community partnerships: Your handbook for action (2nd ed). Corwin Press. Fan, X. (2001). Parental Involvement and Students’ Academic Achievement: A Growth Modeling Analysis. The Journal of Experimental Education, 70(1), 27–61. https://doi.org/10.1080/00220970109599497 Fan, X., & Chen, M. (2001). Parental Involvement and Students’ Academic Achievement: A Meta-Analysis. Educational Psychology Review, 23. Georgiou, S. N., & Tourva, A. (2007). Parental attributions and parental involvement. 10. Gorski, P. (2008). The Myth of the Culture of Poverty. Educational Leadership, 65(7), 32–36. Hamre, B. K., & Pianta, R. C. (2005). Can Instructional and Emotional Support in the First-Grade Classroom Make a Difference for Children at Risk of School Failure? Child Development, 76(5), 949–967. https://doi.org/10.1111/j.1467-8624.2005.00889.x Hill, N. E., & Taylor, L. C. (2004). Parental School Involvement and Children’s Academic Achievement: Pragmatics and Issues. Current Directions in Psychological Science, 13(4), 161–164. https://doi.org/10.1111/j.0963-7214.2004.00298.x Hong, S., & Ho, H.-Z. (2005). Direct and Indirect Longitudinal Effects of Parental Involvement on Student Achievement: Second-Order Latent Growth Modeling Across Ethnic Groups. 11. Hornby, G., & Lafaele, R. (2011). Barriers to parental involvement in education: An explanatory model. Educational Review, 63(1), 37–52. https://doi.org/10.1080/00131911.2010.488049 Hoy, W. K., Tarter, C. J., & Hoy, A. W. (2006). Academic Optimism of Schools: A Force for Student Achievement. American Educational Research Journal, 43(3), 425–446. https://doi.org/10.3102/00028312043003425 Jeynes, W.H. (2014). Parent involvement for urban youth and student of color. In Handbook of urban education (In H. R. Milner&K. Lomotey (Eds.)). NY: Routledge. Jeynes, William H. (2005). Effects of Parental Involvement and Family Structure on the Academic Achievement of Adolescents. Marriage & Family Review, 37(3), 99–116. https://doi.org/10.1300/J002v37n03_06 Jeynes, William H. (2007). The Relationship Between Parental Involvement and Urban Secondary School Student Academic Achievement: A Meta-Analysis. Urban Education, 42(1), 82–110. https://doi.org/10.1177/0042085906293818 Kaplan, D. S., Liu, X., & Kaplan, H. B. (2010). Influence of Parents’ Self-Feelings and Expectations on Children’s Academic Performance. 12. Kuperminc, G. P., Leadbeater, B. J., & Blatt, S. J. (2001). School Social Climate and Individual Differences in Vulnerability to Psychopathology among Middle School Students. Journal of School Psychology, 39(2), 141–159. https://doi.org/10.1016/S0022-4405(01)00059-0 Kutsyuruba, B., Klinger, D. A., & Hussain, A. (2015). Relationships among school climate, school safety, and student achievement and well-being: A review of the literature. Review of Education, 3(2), 103–135. https://doi.org/10.1002/rev3.3043 Long, H., & Pang, W. (2016). Family socioeconomic status, parental expectations, and adolescents’ academic achievements: A case of China. Educational Research and Evaluation, 22(5–6), 283–304. https://doi.org/10.1080/13803611.2016.1237369 Loukas, A. (2007). High-quality school climate is advantageous for all students and may be particularly beneficial for at-risk students. 3. Mattingly, D. J., Prislin, R., McKenzie, T. L., Rodriguez, J. L., & Kayzar, B. (2002). Evaluating Evaluations: The Case of Parent Involvement Programs. Review of Educational Research, 72(4), 549–576. https://doi.org/10.3102/00346543072004549 McWayne, C., Hampton, V., Fantuzzo, J., Cohen, H. L., & Sekino, Y. (2004). A multivariate examination of parent involvement and the social and academic competencies of urban kindergarten children. Psychology in the Schools, 41(3), 363–377. https://doi.org/10.1002/pits.10163 Miedel, W. T., & Reynolds, A. J. (1999). Parent Involvement in Early Intervention for Disadvantaged Children: Does It Matter? Journal of School Psychology, 24. N.A., A., S.A., H., A.R., A., L.N., C., & N, O. (2017). Parental Involvement in Learning Environment, Social Interaction, Communication, and Support Towards Children Excellence at School. Journal of Sustainable Development Education and Research, 1(1), 77. https://doi.org/10.17509/jsder.v1i1.6247 Poon, K. (2020). The impact of socioeconomic status on parental factors in promoting academic achievement in Chinese children. International Journal of Educational Development, 75, 102175. https://doi.org/10.1016/j.ijedudev.2020.102175 Porumbu, D., & Necşoi, D. V. (2013). Relationship between Parental Involvement/Attitude and Children’s School Achievements. Procedia - Social and Behavioral Sciences, 76, 706–710. https://doi.org/10.1016/j.sbspro.2013.04.191 Potvin, R. D. P., & Leclerc, D. (1999). Family Characteristics as Predictors of School Achievement: Parental Involvement as a Mediator. MCGILLJOURNAL OF EDUCATION, 34(2), 19. Reynolds, A. J. (1991). Early Schooling of Children at Risk. 31. Reynolds, A. J. (1992). Comparing measures of parental involvement and their effects on academic achievement. Early Childhood Research Quarterly, 7(3), 441–462. https://doi.org/10.1016/0885-2006(92)90031-S Reynolds, A. J., Ou, S.-R., & Topitzes, J. W. (2004). Paths of Effects of Early Childhood Intervention on Educational Attainment and Delinquency: A Confirmatory Analysis of the Chicago Child-Parent Centers. Child Development,75(5), 1299–1328. https://doi.org/10.1111/j.1467-8624.2004.00742.x Reynolds, A. J., Temple, J. A., Ou, S.-R., Arteaga, I. A., & White, B. A. B. (2011). School-Based Early Childhood Education and Age-28 Well-Being: Effects by Timing, Dosage, and Subgroups. 333, 6. Shute, V. J., Hansen, E. G., Underwood, J. S., & Razzouk, R. (2011). A Review of the Relationship between Parental Involvement and Secondary School Students’ Academic Achievement. Education Research International, 2011, 1–10. https://doi.org/10.1155/2011/915326 Simons-Morton, B. G., & Crump, A. D. (2003). Association of Parental Involvement and Social Competence with School Adjustment and Engagement Among Sixth Graders. 6. Steinberg, L., Lamborn, S. D., Dornbusch, S. M., & Darling, N. (1992). Impact of Parenting Practices on Adolescent Achievement: Authoritative Parenting, School Involvement, and Encouragement to Succeed. Child Development, 63(5), 1266. https://doi.org/10.2307/1131532 Sun, S., Hullman, G., & Wang, Y. (2011). Communicating in the multichannel age: Interpersonal communication motivation, interaction involvement and channel affinity. 9. Sy, S., & Schulenberg, J. (2005). Parent beliefs and children’s achievement trajectories during the transition to school in Asian American and European American families. International Journal of Behavioral Development, 29(6), 505–515. https://doi.org/10.1080/01650250500147329 Thapa, A., Cohen, J., Guffey, S., & Higgins-D’Alessandro, A. (2013). A Review of School Climate Research. 29. Turney, K., & Kao, G. (2009). Barriers to School Involvement: Are Immigrant Parents Disadvantaged? The Journal of Educational Research, 102(4), 257–271. https://doi.org/10.3200/JOER.102.4.257-271 Wong, S. W., & Hughes, J. N. (2006). Ethnicity and Language Contributions to Dimensions of Parent Involvement. School Psychology Review, 35(4), 645–662. https://doi.org/10.1080/02796015.2006.12087968